2020
DOI: 10.1039/c9fo03067k
|View full text |Cite
|
Sign up to set email alerts
|

Milk fermented with Lactococcus lactis KLDS4.0325 alleviates folate status in deficient mice

Abstract: This study proved that milk fermented with L. lactis KLDS4.0325 can alleviate the folate status in deficient mice by animal experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Folate produced by microorganisms has no side effects in the human body ( Jiao et al, 2020 ), but the resulting folate content is relatively low. However, microbial molecular breeding can solve the above problems by transforming strains for specific production purposes to obtain high-yield strains, thereby meeting specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…Folate produced by microorganisms has no side effects in the human body ( Jiao et al, 2020 ), but the resulting folate content is relatively low. However, microbial molecular breeding can solve the above problems by transforming strains for specific production purposes to obtain high-yield strains, thereby meeting specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemically synthesized folic acid and natural folate have different metabolic pathways and mechanisms of action in the human body and have certain side effects. 7 Studies have found that lactic acid bacteria (LABs) in intestinal microorganisms can metabolize and produce vitamins such as folic acid, which is one of the main sources of host vitamins. 8 At the same time, folic acid synthesized by LABs can reduce the side effects caused by the chemical folic acid and has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that folate-producing L. lactis not only effectively increases plasma folate concentrations in mice, but also reduces blood homocysteine levels. 7 Though some LABs cannot synthesize folic acid intact, it has been found that the addition of p-aminobenzoic acid to the medium can greatly increase folate production. 14 In recent years, people often increase their intake of natural folate by supplementing folateproducing LABs or fermented products to prevent and treat chronic diseases in the human body.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations